Analysis of Security and Safety of Tourists at Waterfalls in Gianyar Regency - Cokorda Istri Dharmayanti; Agnes Ayu Biomi; Marniati Marniati (PROMOTOR, 2023)
Background: Nature tourism is in great demand because it offers a different sensation, one of which is waterfalls. Waterfall natural tourism has experienced very rapid development in various places in the province of Bali, one of which is the waterfall in Gianyar district. However, in its development, it has not been balanced with security and safety standards according to the rules that have been set. From the pre-research conducted by the researchers, there were still several incidents at waterfall destinations. There are no handrails on the stairs, the position of the road/stairs is steep and there are no warning signs. Therefore, it is necessary to analyze security and safety so that the researcher raises the title "Analysis of security and work safety of tourists in waterfall tourism in Gianyar Regency". Method: This study uses a descriptive research method with a qualitative approach. The aim is to find out about Occupational Security and Safety at Waterfalls in Gianyar Regency. Results: The results of the analysis show that from observations of waterfall natural tourist destinations in Gianyar Regency, human resources, infrastructure, and warning signs are inadequate from infrastructure and there is no special medical treatment room that should be available to anticipate if an accident occurs on the spot. Conclusion: Tourist Safety and Security in terms of Human Resources factors lack of training needed in handling accidents when they occur, inadequate infrastructure such as stairs and banisters, lack of warning signs such as evacuation routes, and natural factors there are several deficiencies. Natural waterfall destinations need to create work safety and security in that place, workers, tourists, and people who are around these tourist attractions.